(untitled) - John Allen (Cambridge, New York, 1989)
This book provides an anatomy of the nature of private landlordism in the 1980s, the types of landlord in the market, the scope of their activities, and the choices and constraints that guide their actions in the market
Keywords: landlord and tenant - great britain,rental housing - great britain